MODELING JOB SATISFACTION AND PERFORMANCE FROM THE PERSPECTIVES OF JOB ROTATION, WORK DISCIPLINE AND EMPLOYEE DEVELOPMENT - Santoso, Rukun; Hanum, Cholida; Permana, Erwin (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
High employee performance makes it easier for employees to be promoted to higher positions. However, not all employees perform as well as expected by the company, as was the case at PT Adhimix RMC Indonesia. This study aims to model the effect of job rotation perspective variables, work discipline, and employee development on employee performance through job satisfaction mediation. This study employs quantitative research methods and causality analysis. It uses stratified random sampling to collect information. The data were collected using questionnaires, and the partial least square method was used for data analysis. Based on the results of the analysis, job rotation, work discipline, and employee development all have a significant effect on job satisfaction, and job satisfaction influences employee performance significantly. As a result of the analysis, it is also found that job rotation, work discipline, and employee development contribute to employee performance directly or indirectly through job satisfaction. .